2022
DOI: 10.3390/nano12091435
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Phosphides (TMP) as a Versatile Class of Catalysts for the Hydrodeoxygenation Reaction (HDO) of Oil-Derived Compounds

Abstract: Hydrodeoxygenation (HDO) reaction is a route with much to offer in the conversion and upgrading of bio-oils into fuels; the latter can potentially replace fossil fuels. The catalyst’s design and the feedstock play a critical role in the process metrics (activity, selectivity). Among the different classes of catalysts for the HDO reaction, the transition metal phosphides (TMP), e.g., binary (Ni2P, CoP, WP, MoP) and ternary Fe-Co-P, Fe-Ru-P, are chosen to be discussed in the present review article due to their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 177 publications
0
5
0
Order By: Relevance
“…This decrease concerns all kinds of acid sides. It is well known that acid sites play an important role in the mechanism of the triglyceride SDO [ 12 , 38 ]. Papanikolaou et al [ 12 ], working on Ni/zeo-type catalysts, revealed that the proximity between the acidic and the hydrogenation functions led to catalysts with high selectivity to diesel range products enhancing both deCOx and HDO pathways.…”
Section: Resultsmentioning
confidence: 99%
“…This decrease concerns all kinds of acid sides. It is well known that acid sites play an important role in the mechanism of the triglyceride SDO [ 12 , 38 ]. Papanikolaou et al [ 12 ], working on Ni/zeo-type catalysts, revealed that the proximity between the acidic and the hydrogenation functions led to catalysts with high selectivity to diesel range products enhancing both deCOx and HDO pathways.…”
Section: Resultsmentioning
confidence: 99%
“…TMP are created through the alloying of TM with P atoms, whereby the P atoms can influence the electronic conductivity of the material, and thus contribute to the intrinsic electrocatalytic activity of the material. [ 77,78 ] The earliest reported Janus TMP is the Janus Ni 2 P by Stern et al. as active electrocatalysts for H 2 production from both acidic and alkaline waters in 2015.…”
Section: Janus Architecture: Current Developments and Design Strategiesmentioning
confidence: 99%
“…TMP are created through the alloying of TM with P atoms, whereby the P atoms can influence the electronic conductivity of the material, and thus contribute to the intrinsic electrocatalytic activity of the material. [77,78] The earliest reported Janus TMP is the Janus Ni 2 P by Stern et al as active electrocatalysts for H 2 production from both acidic and alkaline waters in 2015. [79] Since then, there has been a surge in Janus TMP for HER electrocatalytic application in view of their excellent HER electrocatalytic activity, which is close to that of state-of-theart Pt/C.…”
Section: Transition Metal Phosphidesmentioning
confidence: 99%
“…9 Therefore, in this study, the guaiacol molecule was also employed to study the DDO reaction because of its higher coking tendency than other phenolic compounds, and also it is a challenging molecule to be totally deoxygenated owing to the co-existence of methoxy and hydroxyl functional groups. 10,11 It is noteworthy to mention that phenol is the OH derivative of benzene and guaiacol is the CH 3 -substituted derivative of phenol, and thereby this variation in molecular structure dictates their different adsorption energetics and reaction kinetics on the Ni 5 P 4 (001) surface.…”
Section: Introductionmentioning
confidence: 99%